Examination on the Aggression Levels of Turkish National Skiing Athletes - Gacar, Atalay (Annals Applied Sport Science, 2015)
Leading the aggression in some athletes ensures productivity; however, misleading does not give the same result. The aggression may reach dangerous extents. Nevertheless, aggressive behavior can be regarded as a relaxation. One of the important reasons of violence and aggression seen in sports is the belief that it increases the performance or success. Based upon these arguments, we aim to examine the aggression levels of Turkey national skiing athletes. The study has been conducted on 9 female and 11 male national skiing athletes who participated in International Alpine Skiing Cup held in Sarikamis in 2012. An assessment instrument that comprises 2 parts was used to acquire data. At the first part, demographic data of the participants were gathered; at the second part, a 30-item Aggression Scale of which reliability has been developed by Ipek Ilter was used to analyze the participants' aggression and factors influencing aggression. Consequently, the aggression levels were observed below the average pursuant to the gender, age and year of sports. Furthermore, assertiveness level was observed as high while disruptive and passive dimensions of aggression were found low. It is believed the athletes' being national athletes at the elite level has importance in both team success and individual success.
Keywords: Sports; Turkish National Team; Skiing; Aggression; Assertiveness